2017
DOI: 10.4103/ijo.ijo_344_16
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative posterior capsular striae and the posterior capsular opacification in patients implanted with two types of intraocular lens material

Abstract: Aim:To evaluate the incidence of postoperative posterior capsular striae (PCS) and its influence on posterior capsular opacification (PCO) in patients implanted with two types of lens material.Setting:Tertiary eye care center in central rural India.Study Design:A prospective, observational, nonrandomized study.Materials and Methods:The study included 1247 patients having age-related cataract scheduled for removal by phacoemulsification technique and implantation of hydrophilic or hydrophobic intraocular lens (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the present study, IOL materials were either hydrophobic or hydrophilic. Previous studies have reported that the incidence of PCO in patients implanted with hydrophilic lenses is higher than the in patients implanted with hydrophobic lenses [ 24 ]. However, some studies have reported that the incidence of PCO using hydrophilic lenses is less than in patients using hydrophobic lenses [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, IOL materials were either hydrophobic or hydrophilic. Previous studies have reported that the incidence of PCO in patients implanted with hydrophilic lenses is higher than the in patients implanted with hydrophobic lenses [ 24 ]. However, some studies have reported that the incidence of PCO using hydrophilic lenses is less than in patients using hydrophobic lenses [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies about Nd:YAG capsulotomy rates evaluation showed hydrophilic lenses had statistically higher Nd:YAG capsulotomy rates than hydrophobic lenses. 4,16,17 In this study, although there are slight differences in the design of the two kinds of multifocal IOLs, their optical configurations are dihedral aspheric surface with square edges, the multifocal design is located on the front surface, the back surface is aspheric, and the haptic angulation is 0°. In terms of materials, both are hydrophilic multifocal IOLs, but diffractive MIOL has a hydrophobic surface.…”
Section: Discussionmentioning
confidence: 88%
“…Acrylic material is associated with reduced PCO rate by causing a lower postoperative inflammation than the previously used materials [9]. In addition, lenses with sharp edge design have better outcomes by the inhibition of lens epithelial cells' (LECs) migration [16].…”
Section: Discussionmentioning
confidence: 99%